The films of Konrad Wolf : archive of the revolution - Powell, Larson, 1960- (Camden House, 2020)
"This is the first book in any language on the films of Konrad Wolf (1925-1982), East Germany's greatest filmmaker, and puts Wolf in a larger European filmic and historical context"-- Provided by publisher
Keywords: Wolf, Konrad, -- 1925-1982 -- Criticism and interpretation.; Wolf, Konrad, -- 1925-1982; Motion pictures -- Germany (East) -- History.; Cinéma -- Allemagne (Est) -- Histoire.; PERFORMING ARTS -- Film & Video -- History & Criticism.; Motion pictures; Germany (East); Aesthetic Conscience.; Antifascist Films.; Archive of the Revolution.; Brecht.; East Germany's Greatest Filmmaker.; European Filmic.; Everyday Life.; Fassbinder.; Filmic Forms.; Films of Konrad Wolf.; Generic References.; German-Language Films.; Historical Context.; Konrad Wolf.; Musical.; Political Function.; Tarkovsky.; Wajda.; Criticism, interpretation, etc.; History